Hedgehog and extramacrochaetae in the Drosophila eye: An irresistible force meets an immovable object - Spratford, Carrie M (Landes Bioscience, 2014)
During the third and final larval instar stage, thousands of pluripotent cells within the Drosophila eye imaginal disc are transformed into a near perfect neurocrystalline lattice of 800 unit eyes called ommatidia. This transformation begins with the initiation of the morphogenetic furrow at the posterior margin of the eye field. The furrow, which marks the leading edge of a wave of differentiation, passes across the epithelium transforming unpatterned and undifferentiated cells into rows of periodically spaced clusters of photoreceptor neurons. As cells enter and exit the furrow they undergo dramatic alterations in cellular architecture and gene expression, many of which are required to propel the furrow forward and for proper cell fate specification. The Decapentaplegic (Dpp) and Hedgehog (Hh) signaling pathways are required for the initiation and progression of the furrow, respectively. Consistent with a role in furrow progression, the loss of Hh pathway activity results in a “furrow stop” phenotype. In contrast, reductions in levels of the helix-loop-helix transcription factor, Extramacrochaetae (Emc), lead to the polar opposite phenotype—the furrow accelerates. Recently, we demonstrated that the furrow stop and furrow acceleration phenotypes are molecularly connected. Emc appears to serve as a brake on the furrow by dampening the activity of the Hh pathway. Loss of Emc leads to an upsurge in Hh pathway activity and a faster moving furrow. The acceleration of the furrow appears to be due to an increase in levels of the full-length isoform of Cubitus Interruptus (Ci(155)) and Suppressor of Fused [Su(fu)]. Here we will briefly review the mechanisms by which Hh drives and Emc impedes the progression of the furrow across the developing retina.